Isolamento e caracterização de locos microssatélites e análise da variabilidade genética de duas populações de anopheles (n.) Triannulatus sensu latu (diptera: culicidae) da cidade de Manaus - Cruz , Paula Figliuolo da (2011)
Anopheles triannulatus is a complex of cryptic species consisting of at least three species: Anopheles triannulatus ss, Anopheles halophylus and another until now not identified species named A. triannulatus C. Yet, A. triannulatus is a zoophilic, twilight and exophilic species. Nevertheless, A. triannulatus has endophagous and anthropophilic abilities. The importance of anopheles triannulatus as a transmitter of human malaria is still an issue. A. triannulatus has been found infected with Plasmodium vivax and Plasmodium falciparum, so is being considered as a possible vector of malaria in Venezuela. Given this, and that its taxonomic status lies upon controversies, it is constructed in this work a genomic library enriched with microsatellites (SSRs) which were analyzed in two populations from the Amazon Region. That library has generated 96 clones with inserts and 84 nucleotide sequences of good quality. Of the 75 contigs obtained, 83 sequences showed to contain SSRs with only 1.31% of inherent redundancy. 51 primers pairs were isolated, from which 15 loci microsatellites were characterized in 25 individuals of A. triannulatus collected in the neighborhood of the site Puraquequara, in the city of Manaus, in Amazonas State, Brazil. The work also shows were obtained 88 alleles, ranging from 3 to 10 alleles per locus, with an average of 6.0 alleles. The observed heterozygosity (HO) ranged from 0.157 to 0.866, while expected heterozygosity (HE) ranged between 0.322 to 0.843. The amplification of 15 heterologous microsatellite loci revealed four loci, amplified for all species (A. benarrochi, A. rangeli, A. oswaldoi and A. darlingi), and four amplified loci for at least one species. For the analysis of genetic variability eight loci were selected in which more polymorphism and number of individuals were genotyped. For those eight loci, 71 alleles were obtained with an average of 6.25 and 7.25 alleles per locus, at Puraquequara and Janauari river, respectively. Both population have shown observed heterozygosity ranging from respectively 0.318 to 0.937 and from expected 0.455 to 0.838, what indicates high genetic variability. The Wright's F statistics showed high genetic structure among populations (FST = 0.282), what is a fair indication of interspecific differentiation for complex species, what is confirmed, by one side, by the high figure for the genetic distance between the two populations (D = 1.832), and by another side, by the results of the implemented Bayesian analysis, performed with the aid of the computational software STRUCTURE , which revealed the existence of two clusters (K = 2) taking into account two distinct populations.